Physical, chemical and biological properties of MTA Angelus and novel AGM MTA: an in vitro analysis - Sara Nashibi; Parisa Amdjadi; SeyedehSana Ahmadi; Sara Hekmatian; Maryam Torshabi (BMC Oral Health, 2025)
Abstract Introduction Mineral trioxide aggregate (MTA) is a calcium silicate-based cement that has changed conventional dental therapeutic approaches. This study aimed to evaluate physical, chemical and biological properties of novel AGM MTA, in comparison with MTA Angelus. Methods The samples were prepared according to the manufacturer’s instructions. The initial and final setting times were measured via a Gillmore needle following the ISO 6876:2012 standard. The radiopacity of the materials was evaluated against an aluminium step wedge on the basis of the ISO 6876 and 13,116 standards. The pH changes were measured at intervals of 3, 6, 24, 72, 96 and 144 h postimmersion in Hank’s solution and calcium ion release was analysed after 168 h of immersion via inductively coupled plasma optical emission spectroscopy (ICP‒OES). Moreover, the cytotoxicity was assessed through the MTT assay on human dental pulp stem cells (hDPSCs) after 24 and 72 h of exposure to the set/fresh status of various dilutions of MTA extracts, following the ISO 10993-12 standard. Results No significant difference was found between the initial setting times of the two materials (Angelus: 11.0 ± 1.0 min, AGM: 10.3 ± 1.5 min); however, MTA Angelus demonstrated a significantly shorter final setting time. Both materials met the minimum radiopacity requirements according to the ISO 6876 standard, with MTA Angelus exhibiting greater radiopacity than AGM MTA. Both materials created an alkaline environment without presenting any differences in each time point and AGM MTA released significantly greater amounts of calcium ions. In the cytotoxicity assessment, while the diluted extracts of both materials did not elicit any cytotoxic effects, the nondiluted samples, after 72 h of exposure, as well as the 30-min set AGM MTA after 24 h of exposure, were shown to be cytotoxic. Conclusions In conclusion, MTA Angelus presented a faster setting time and lower cytotoxicity, while AGM MTA demonstrated greater calcium ion release. However, both materials presented clinically acceptable properties and AGM MTA could be a potential alternative to MTA Angelus. However, further clinical studies are required to confirm its application.